Digital Transformation of Hospital Information Management System (SIMRS) as an Organizational Performance Improvement Strategy: A Literature Review - Alendra Chakramurty; Chichie Winnie Nasution; Purwadhi Purwadhi; Yani Restiani Widjaja (CV. Publikasi Indonesia, 2026)
Digital transformation in the health sector has become a global and national priority agenda. Hospital Management Information System (SIMRS) is the backbone of digital transformation in healthcare institutions. This study aims to examine the role of SIMRS as a management strategy that drives improvements in hospital organizational performance through a systematic literature review. The method used was narrative literature review by analyzing 20 articles published in 2020–2024 from PubMed, Garuda, and Google Scholar databases. The results show that integrative SIMRS implementation has been proven to improve operational efficiency (average waiting time reduction of 35–45%), clinical data accuracy, patient satisfaction, and support data-driven strategic decision-making. However, main challenges include human resource resistance, infrastructure limitations, and weak data governance. The success of digital transformation requires strategic leadership, organizational readiness, continuous HR training, and system integration with accreditation platforms (KARS/JCI). This study concludes that SIMRS is not merely a technological tool, but a strategic management instrument that, when comprehensively implemented, will enhance the competitiveness and sustainability of hospitals in the era of National Health Insurance.